Altered function of the glutamate–aspartate transporter GLAST, a potential therapeutic target in glioblastoma. Issue 10 (5th January 2019) - Corbetta, Cristina; Di Ianni, Natalia; Bruzzone, Maria Grazia; Patanè, Monica; Pollo, Bianca; Cantini, Gabriele; Cominelli, Manuela; Zucca, Ileana; Pisati, Federica; Poliani, Pietro Luigi; Finocchiaro, Gaetano; Pellegatta, Serena
Abstract : In glioma patients, high levels of glutamate can cause brain edema and seizures. GLAST, a glutamate–aspartate transporter expressed by astrocytes with a role in glutamate uptake, is highly expressed on the plasma membrane of glioblastoma (GBM) cells, and its expression significantly correlates with shortened patient survival. Here, it was demonstrated that inhibition of GLAST expression limited the progression and invasion of GBM xenografts. Magnetic resonance spectroscopy was used to measure glutamate in GLAST‐expressing gliomas showing that these tumors exhibit increased glutamate concentration compared to GLAST‐depleted glioma. Despite their GLAST expression, GBM stem‐like cells (GSCs) released rather than taking up glutamate due to their lack of Na+/K+‐ATPase. Overexpression of Na+/K+‐ATPase in these cells restored glutamate uptake and induced apoptosis. The therapeutic relevance of targeting GLAST in gliomas was assessed using the inhibitor UCPH‐101. In glioma‐bearing mice, a single intratumoral injection of UCPH‐101 significantly increased survival by decreasing GLAST expression and inducing apoptosis. Thus, GLAST has a novel role in GBM that appears to have crucial relevance in glutamate trafficking and may thus be a new therapeutic target. Abstract : What's new? Increased expression of the cystine/glutamate antiporter xCT is associated with glutamate‐promoted glioblastoma (GBM) invasion into surrounding brain tissue. In this study, GLAST, an astrocyte transporter physiologically devoted to glutamate uptake, was also found to serve a role in GBM aggressiveness. GLAST was highly expressed in GBM specimens and, in association with Na+/K+/ATPase downregulation, exhibited impaired glutamate uptake, resulting in elevated extracellular glutamate levels and GMB cell protection against apoptosis. GLAST inhibition, by contrast, decreased extracellular glutamate, increased GBM cell apoptosis, and prolonged survival in glioma‐bearing mice. The findings provide preliminary background for translational research of GLAST inhibitors.